The martyrdom and miracles of Saint George of Cappadocia - George, Saint d. 303 (Oriental text series, 1888)
Preface.--The martyrdom of Saint George.--The encomium upon Saint George by Theodosius, bishop of Jerusalem.--The miracles of Saint George.--The encomium upon Saint George by Theodotus, bishop of Ancyra.--Fragments of a Sahidic version of the martyrdom of Saint George.--English translation.